MANAJEMEN KEUANGAN MADRASAH - Muhammad Roihan Daulay (Al-Muaddib : Jurnal Ilmu-Ilmu Sosial & Keislaman, 2017)
The   title   of   this   paper   is   financial   management   of Madrasah. To form the high quality of Islamic education so it would   be   need   to   have   the   effective,   accountable,   and transparent  financial  management.  The  importance  of  this would  mention  such  as  planning,  operating, implementation, evaluation  of  the  madrasah  financial,  including  of  madrasah ibtidaiyah,   tsanawiyah   and   aliyah   becomes   an   important point to recognize.  By the realization of financial management based on the above  principle,  it  is  hoped  the  madrasah  would  be  better. However,  if  the  financial  management  were  not  suitable  to those  principles,  as  the  result  it  will  be  fail  to  educated  the youth generation